Sulle “nuove” condizioni costituzionali di candidabilità per la Presidenza della Romania e sui nodi irrisolti della Curtea Constituțională (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
On the “new” constitutional conditions for eligibility for the Presidency of Romania and on the unresolved issues of the Curtea ConstituționalăThe essay addresses the issue of Romania's presidential election from the perspective of eligibility conditions. In particular, it focuses on the new axiological framework introduced by the Constitutional Court since ruling no. 2 of October 5, 2024, when the Constitutional Judges have laid down the occurrence of new substantive conditions of general order related to the observance of the fundamental values enshrined in the Constitution. On these assumptions, the Author critically addresses the original Constitutional Court’s decision and some subsequent rulings from which emerges an unclear jurisprudential framework, which may produce a negative impact in the middle and long term.
Keywords: Romania; Presidential Election; Constitutional Court; European Union; Eligibility